2018
DOI: 10.1038/s41433-018-0239-4
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of submacular haemorrhage (SMH) in Scotland: a Scottish Ophthalmic Surveillance Unit (SOSU) study

Abstract: Purpose Submacular haemorrhage (SMH) is a cause of severe visual loss in neovascular age-related macular degeneration (nAMD). The incidence is uncertain and furthermore there is no widely used classification system nor agreed best practice. The aim of this national surveillance study was to identify the incidence, presenting features and clinical course of new fovea-involving submacular haemorrhage associated with nAMD. Methods A questionnaire was sent monthly to every ophthalmic specialist in Scotland over a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Few studies have investigated the incidence and rate of this uncommon and potentially severe complication of nAMD. A nationwide prospective observational study using SOSU (Scottish Ophthalmic Surveillance Unit) found an overall incidence of 5.4 SMH (defined as all newly diagnosed cases of fovea-involving SMH of size >2 disc diameters) per million per annum (Al-Hity et al 2019). In relation to the number of patients with exudative AMD (about 1.4% of the population of Europe), this rate (about 5.4 per 14 000 versus 64 per 14 000 in our study) is somewhat lower than in our study (Li et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have investigated the incidence and rate of this uncommon and potentially severe complication of nAMD. A nationwide prospective observational study using SOSU (Scottish Ophthalmic Surveillance Unit) found an overall incidence of 5.4 SMH (defined as all newly diagnosed cases of fovea-involving SMH of size >2 disc diameters) per million per annum (Al-Hity et al 2019). In relation to the number of patients with exudative AMD (about 1.4% of the population of Europe), this rate (about 5.4 per 14 000 versus 64 per 14 000 in our study) is somewhat lower than in our study (Li et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Many of our patients were referrals from other centers (our institute is one of the largest tertiary centers in Korea), but the high number of patients with RVO and AMD-related submacular hemorrhage encountered within a short period (~4 months) indicates that these uncommon pathologies did not develop by chance. Submacular hemorrhage is known to occur in 5.4 per million, which indicates that this is not a condition seen every day in a retina clinic [ 26 ]. According to a study including 791 newly diagnosed neovascular AMD patients, 129 eyes (16.3%) exhibited submacular hemorrhage at initial presentation, and the incidence of submacular hemorrhage was greater in PCV (23.6%, 78 of 330 eyes) than in typical neovascular AMD (9.4%, 28 of 297 eyes) [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…To account for this, the size of macular hemorrhage was also assessed using color fundal photographs based on following modified criteria (example shown in Figure 2): small (from one optic nerve disk diameter to four optic nerve disk diameters), medium (larger than four optic nerve disk diameters, but within temporal vessel arcades), and massive (hemorrhage extending beyond temporal arcades). 14…”
Section: Methodsmentioning
confidence: 99%